2019
DOI: 10.1101/2019.12.16.877878
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Dynamic Landscape of Transcription Initiation in Yeast Mitochondria

Abstract: 12Controlling efficiency and fidelity in the early stage of mitochondrial DNA transcription is 13 crucial for regulating cellular energy metabolism. Studies of bacteriophage and bacterial 14 systems have revealed that transcription occurs through a series of conformational transitions 15 during the initiation and elongation stages; however, how the conformational dynamics 16 progress throughout these stages remains unknown. Here, we used single-molecule 17 fluorescence resonance energy transfer techniques to e… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 47 publications
2
12
1
Order By: Relevance
“…This observation is consistent with single-molecule fluorescence studies showing that T7 and bacterial RNAPs remain stably bound to the promoter during abortive synthesis (Koh et al, 2018;Revyakin et al, 2006). Continuous scrunching/unscrunching, which we infer is occurring on the basis of the coexistence of both states in solution, is consistent with a recent single-molecule FRET study of y-mtRNAP where dynamic switching between scrunched and unscrunched states was observed throughout transcription initiation (Sohn et al, 2020). The dynamic equilibrium between IC and PmIC states in our study suggests that in an abortive event, the scrunched IC state switches to the unscrunched PmIC state, which will then rebind the NTPs to start a fresh cycle of RNA synthesis.…”
Section: The Mtf1 C-tail Plays a Central Role In Transcription Initiasupporting
confidence: 92%
See 4 more Smart Citations
“…This observation is consistent with single-molecule fluorescence studies showing that T7 and bacterial RNAPs remain stably bound to the promoter during abortive synthesis (Koh et al, 2018;Revyakin et al, 2006). Continuous scrunching/unscrunching, which we infer is occurring on the basis of the coexistence of both states in solution, is consistent with a recent single-molecule FRET study of y-mtRNAP where dynamic switching between scrunched and unscrunched states was observed throughout transcription initiation (Sohn et al, 2020). The dynamic equilibrium between IC and PmIC states in our study suggests that in an abortive event, the scrunched IC state switches to the unscrunched PmIC state, which will then rebind the NTPs to start a fresh cycle of RNA synthesis.…”
Section: The Mtf1 C-tail Plays a Central Role In Transcription Initiasupporting
confidence: 92%
“…The co-existence of PmIC and IC states suggests a dynamic equilibrium between the two states. A recent single-molecule FRET study of transcription initiation observed dynamic equilibrium among intermediate IC states of y-mtRNAP (Sohn et al, 2020). From the cryo-EM dataset, the final density maps for y-mtRNAP IC and y-mtRNAP PmIC structures were calculated at 3.7 Å and 3.5 Å resolution, respectively (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations